2017
DOI: 10.1111/jbi.13125
|View full text |Cite
|
Sign up to set email alerts
|

Demographic modelling reveals a history of divergence with gene flow for a glacially tied stonefly in a changing post‐Pleistocene landscape

Abstract: Aim Climate warming is causing extensive loss of glaciers in mountainous regions, yet our understanding of how glacial recession influences evolutionary processes and genetic diversity is limited. Linking genetic structure with the influences shaping it can improve understanding of how species respond to environmental change. Here, we used genome‐scale data and demographic modelling to resolve the evolutionary history of Lednia tumana, a rare, aquatic insect endemic to alpine streams. We also employed a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…A distinct genetic cluster composed of individuals from Rennell Sound (REN) on the west coast of Haida Gwaii that was well separated from the other sites in the northern regional group was detected by DAPC, but not by the analysis of individual ancestry (ADMIXTURE). This outcome is in agreement with previous studies showing that DAPC is more efficient than other clustering methods at detecting genetic subdivisions when overall genetic differentiation is weak (Benestan et al., ; Hotaling et al., ; Jombart et al., ). Using hierarchical clustering of pairwise F ST , we showed that REN was significantly differentiated from other sampling locations, thus further corroborating the DAPC results, as were the two sites sampled on the west coast of Vancouver Island (TOF and QUA).…”
Section: Discussionsupporting
confidence: 93%
“…A distinct genetic cluster composed of individuals from Rennell Sound (REN) on the west coast of Haida Gwaii that was well separated from the other sites in the northern regional group was detected by DAPC, but not by the analysis of individual ancestry (ADMIXTURE). This outcome is in agreement with previous studies showing that DAPC is more efficient than other clustering methods at detecting genetic subdivisions when overall genetic differentiation is weak (Benestan et al., ; Hotaling et al., ; Jombart et al., ). Using hierarchical clustering of pairwise F ST , we showed that REN was significantly differentiated from other sampling locations, thus further corroborating the DAPC results, as were the two sites sampled on the west coast of Vancouver Island (TOF and QUA).…”
Section: Discussionsupporting
confidence: 93%
“…before the last glacial maximum in the Rocky Mountains ~20,000 years ago, Carrara, 1987). This timeline is supported by estimates of divergence timing among L. tumana genetic clusters in GNP, which placed intraspecies splits as occurring in the last ~18,000 years (Hotaling et al, 2018). Conversely, Z. glacier may have more recently invaded headwaters, possibly due to range contraction into higher elevations to follow the retreat of glaciers (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…Automated big data phylogeography represents an important direction for the field. While single species studies, particularly those that utilize multilocus data (e.g., Hotaling et al., ), can compare a broad range of detailed models, and comparative studies into a single system enable a more nuanced investigation of how changes in the landscape have influenced evolutionary history (e.g., Mather, Hanson, Pope, & Riginos, ), neither has the potential to uncover generalized patterns on continental or global scales. Automated studies can incorporate organismal trait data in a manner that is not possible in more limited studies, which offers an important connection between evolutionary and ecological processes (Rissler, ).…”
Section: Discussionmentioning
confidence: 99%